Study on cutaneous manifestation among type II diabetes mellitus in rural Pondicherry, India - ., Kandaswamy; P., Kanagarajan; K., Suganthi; A., Lokeshmaran (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes has emerged as a major public health care problem in India. According to Diabetes atlas published by the International Diabetes Federation (IDF), there was on 2007 an estimated 40.9 million people with diabetes in India and this number is predicted to rise to almost 69.9 million people by 2025. The skin is affected by both the acute metabolic derangements and the chronic degenerative complications of diabetes. Cutaneous signs of diabetes mellitus are extremely valuable to the clinician as some of them can alert the physician to the diagnosis of diabetes and also reflect the status of glycemic control and lipid metabolism. The objective was to study the cutaneous manifestations in patient with type II diabetes mellitus. Method: The present cross sectional study was conducted at field based area of Mahatma Gandhi Medical College and Research Institute, Puducherry, India from January 2013 to June 2013. Data collection was done using pretested proforma and information regarding age, sex, duration of diabetes, treatment, blood glucose (Fasting, Post prandial), urine examination, specific investigations and skin lesions were taken. A complete physical and dermatological examinations of the patients was done. Statistical analysis was done. Results: Among the total number of 166 patients studied, there were 44 (26.50%) women and 122 (73.49%) men; the male: female ratio was 3:1, of the total diabetic patients, majority 85 (51.2%) had <5 years of duration of diabetes. Among the cutaneous disorders found in patients with diabetes, majority of the patients had cruralcandidal intertrigo and patients each had acquired ichthyosis and tineacruris. Trophic ulcer and xerosis were found in 8% patients followed by furunclosis and psoriasis vulgaris seven percent (7%). Conclusion: The failure to give adequate skin care in patients with diabetes may be attributed to lack of patient’s knowledge of the disease.